DOUBLE ENTRY JOURNAL TECHNIQUE FOR THE STUDENTS’ READING COMPREHENSION - Bahrun Amin (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2012)
The objective of the research is to know the improvement of the students’ reading comprehension using double entry journal technique at the second year students’ of SMA Neg. 1 Pasui. This research is a classroom action research consist of two cycles, the mean score of the students’ reading comprehension for diagnostic-Test is 5.95 which is categorized as poor classification. While the mean score of the students’ reading comprehension in cycle I was 6.39. It is higher than the students’’ D-Test. But the result was still not significant because it is still categorized as fair and under the KKM 60. So the research is continued to the cycle II and the mean score of the students’ reading comprehension of cycle II was 6.82. Having analyzed the data, it can be stated that the students’ reading comprehension at the second year in class XI of SMA Neg.1 Pasui is poor level before applying the double entry journal technique, but after applying the technique in the second cycle, the students’ reading comprehension is classified as good categories.